MENGKAJI PRAKTIK PEMBLOKIRAN HARTA KEKAYAAN PENANGGUNG PAJAK (STUDI DI KANTOR PELAYANAN PAJAK PRATAMA MADIUN) - Nikita Puspa Wisiswa; Irwan Aribowo (Politeknik Keuangan Negara STAN, 2021)
One of the efforts to reduce tax arrears is through tax collection in the form of account blocking. The implementation of Perpu Number 1 of 2017 concerning Access to Financial Information for Tax Purposes also has an impact on the output and outcome of the account blocking process. The obstacles that occurred during the blocking came from the banking and tax guarantor side, from the bank side mostly caused by dissimilarity of understanding and policies related to account blocking between the Directorate General of Taxes and the Bank, while from the tax guarantor side generally is in the form of changes in the deed during the blocking process, bankruptcy and/or death of the tax bearers. In its efforts to prevent and overcome these obstacles, there is also a Letter from the Director General of Taxes Letter Number 20 of 2018 concerning Confirmation of the implementation of Blocking, Prevention, and hostage taking.